2020
DOI: 10.3390/ijerph17124380
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Impact of Intergenerational Support on Depressive Symptoms among Older Adults in Korea

Abstract: Background: This study examined the relationship between intergenerational support patterns and depressive symptoms among older men and women in Korea. Methods: A nationally representative survey of non-institutionalized, community-dwelling older adults in Korea was used. A total of 7531 older adults (3592 men and 3939 women) was included in the analysis. Results: We observed gender differences in the impact of financial support exchanges on depressive symptoms. A lack of mutual financial support significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…In this study, women’s low NQ-E scores were primarily due to low scores for dietary behavior, which includes questions about difficulties in chewing foods, perception of one’s health, depressive symptoms, handwashing practices before eating meals, hours of exercise, and efforts to have healthy eating habits. Among the participants in this study, 40.9% of elderly women was living alone, which was higher than the 27.4% reported in another study [ 29 , 30 ]. Thus, it may be that women reported more depressive feelings because of the length of time they lived alone, which tends to be longer for women than for men due to differences in life expectancy.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, women’s low NQ-E scores were primarily due to low scores for dietary behavior, which includes questions about difficulties in chewing foods, perception of one’s health, depressive symptoms, handwashing practices before eating meals, hours of exercise, and efforts to have healthy eating habits. Among the participants in this study, 40.9% of elderly women was living alone, which was higher than the 27.4% reported in another study [ 29 , 30 ]. Thus, it may be that women reported more depressive feelings because of the length of time they lived alone, which tends to be longer for women than for men due to differences in life expectancy.…”
Section: Discussioncontrasting
confidence: 69%
“…Filial piety is a traditional Chinese cultural value that urges children to respect and take care of their parents [ 8 ]. Children’s intergenerational support is often an important guarantee for older adults to obtain subjective well-being, which may alleviate depression in older adults [ 9 , 10 , 11 , 12 ]. Study had shown that pensions affected children’s intergenerational support for their older parents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, an individual’s perception of family relationships is mainly influenced by the filial piety, a central concept in Confucian culture [ 21 ]. Meanwhile, other eastern countries, such as Japan, also have strong norms of family obligation and filial norms about caring for older parents [ 22 ]. Thus, family members, especially adult children, are expected to take care of and support the elderly, and the family support seems to become an important source of living satisfaction and well-being for aging adults [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%